ESTABILIDAD ESTRUCTURAL DE SUELOS EN ZONA DE SELVAS NUBLADAS DE LOS ANDES DE MÉRIDA, VENEZUELA - Vera, Mauricio; López, Roberto (Venesuelos, 2011)
Palabras clave: Estabilidad estructural del suelo, selvas nubladas, pastizal, andes venezolanos, Mérida Abstract A research was conducted in order to study the water structural stability of nine soils (Humoxic Tropohumults, Vertic Tropo-humults, Oxic Humitropepts y Troporthods) developed under cloudy forest bioclimatic zone in Merida state, Venezuela. The study considered land use (forest-grasses) and parent material as the factors (independent variables) that affect soil structural stability which was evaluated using the modified Yoder methodology. Soils under forest and those under grasses presented contrasting morphological characteristics, but not statistical significant differences were detected in soil structural stability as influenced by differences in land use conditions. Five out of the nine soils showed moderate to high structural stability, the other four soils were catalogued as materials of low to very low structural stability. Such a condition seems to be related to differences in soil parent materials which condition in a high degree the physical-chemical properties of these soils. Key words: soil structural stability, cloudy forest, grassland, Andes, Mérida